Population dynamics of Walia ibex (Capra walie) at Simien Mountains National Park, Ethiopia - Alemayehu, K.; Dessie, Tadelle; Gizaw, Solomon; Haile, Aynalem; Mekasha, Yoseph (Wiley, 2011)
Intensive total direct counts of Walia ibex (Capra walie) population were performed at Simien Mountains National Park (SMNP) in 2009. Historical data were collected from SMNP and literature reviews. Different models were suited to determine population growth rates and intrinsic rate of increase. The population size estimated was 745 animals. The correlation between the two repeated counts was significant (r = 0.99 and P < 0.01). Mean instantaneous growth rate (r), growth rate per capita (λ) and population annual growth rate (Λ) were 2.6 ± 2.6, 0.03 ± 0.18 and 19.5 ± 50.4, respectively. Instantaneous growth rate and growth rate per capita were positively correlated (r = 0.958, P < 0.01). Average growth rate (rΛ) and intrinsic rate of increase (rr) under ideal (r = 0.950, P < 0.01) and random environments (r = 0.810, P < 0.01) were positively correlated. The population grows by 2.5% under ideal environments with an intrinsic increase of 0.04 (0.006%) and by 0.13% under random environments with intrinsic rate of decrease of −0.184 or −0.025% per year, respectively. The mean rank of the flock structure of whole population was 3.13, 3.88, 2.00 and 1.00 for males, females, juveniles and unidentified, respectively.